PENERAPAN AJEN ATIKAN UNTUK ANAK-ANAK KOMUNITAS HONG MELALUI SENI KAKAWIHAN KAULINAN BARUDAK BUHUN DALAM UPAYA MEMBINA KESALEHAN BUDAYA - Mayakania, Nia Dewi (Universitas Pendidikan Indonesia, 2016)
The study is motivated by many indicators that show the moral degradation of the children. This phenomenon was anticipated by Komunitas Hong to instill ajen atikan through Kakawihan Kaulinan Barudak Buhun (KKBb). The results showed that in the socio-cultural context, KKBb has a dominant function in building a human life. Practically, the ajen atikan internalization process is based on the concept of Komunitas Hong; knowing the nature, the culture, and the God. The KKBb’s values is thought through habituation and exemplary system. While the ajen atikan internalization strategies made through efforts to activate the affective domain, to foster positive behavior repeatedly, and the transfer of value in a certain way. As for ajen atikan (moral values) that learned revolves around the planting ajen atikan which is essentially virtues. Basically, the values are the hidden curriculum that is integrated directly in the whole element of KKBb.